2016
DOI: 10.1177/1076029615604049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankaferd Blood Stopper on Skin Superoxide Dismutase and Catalase Activities in Warfarin-Treated Rats

Abstract: Ankaferd Blood Stopper acted positively in short-term tissue healing by increasing SOD activity in warfarin-treated rats. Therefore, ABS may be suggeted as a promoting factor in tissue healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…When the hemostatic efficiency of adrenaline and ABS was compared on 20 patients requiring orthodontic intervention, bleeding time was found to be significantly shorter in the ABS group compared to the adrenaline group 26 . Aktop et al 27 , in a study in which they evaluated tissue healing, ABS was showed a positive effect on short-term tissue healing by increasing superoxide dismutase (SOD) activity in rats treated with warfarin. In comparison of ABS and Surgicel in subjects with experimental liver laceration; rats in the ABS and Surgicel groups survived significantly longer than rats in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…When the hemostatic efficiency of adrenaline and ABS was compared on 20 patients requiring orthodontic intervention, bleeding time was found to be significantly shorter in the ABS group compared to the adrenaline group 26 . Aktop et al 27 , in a study in which they evaluated tissue healing, ABS was showed a positive effect on short-term tissue healing by increasing superoxide dismutase (SOD) activity in rats treated with warfarin. In comparison of ABS and Surgicel in subjects with experimental liver laceration; rats in the ABS and Surgicel groups survived significantly longer than rats in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…ABS has been used as a local haemostatic agent in surgery, but it was also shown to promote healing (5,9). Its effects on soft-tissue healing have been investigated (17,(19)(20)(21), but not in a STZ model of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the healing potential of particular agents in animal models of diabetes, examining clinical effects or histological outcomes (24)(25)(26)(27). ABS has been used as a local haemostatic agent in surgery, but it was also shown to promote healing (5,9). Its effects on soft-tissue healing have been investigated (17,(19)(20)(21), but not in a STZ model of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations